Pengaruh Computer Self Efficacy (CSE) Terhadap Computational Thinking Siswa Pada Mata Pelajaran Informatika di SMP Negeri 1 Salatiga - Siti Nur Afiah; Angela Atik Setiyanti; Krismiyati Krismiyati (Peneliti.net, 2023)
Informatics subjects are subjects that study ICT content extensively or broadly. In informatics subjects students often use computer devices. Computer Self Efficacy (CSE) namely self-confidence in operating a computer. CSE as one of the most important variables in the field of information technology. CSE plays an important role in informatics subjects. A good CSE supports students in informatics learning activities. Computational thinking as a way to solve a complex problem by applying computational methods and concepts in computer science. This research was conducted to determine the effect of computer self-efficacy (CSE) on students' computational thinking in informatics subjects. The research method used in this study was a quantitative inferential method with a sample of 259 respondents. The research was conducted at SMP Negeri 1 Salatiga. Based on the results of the research that has been carried out, it is known that CSE has an influence on students'.